Analisis Kapasitas Kolam Retensi untuk Pengendali Banjir di Perumahan Siliwangi Green Residence Kecamatan Baleendah, Kabupaten Bandung - Iing Rustandi; Raisa Fadhila; Rully Savitri Nurvita (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The synthetic unit hydrograph methods of Nakayasu, HEC-HMS (Snyder), SCS, ITB-1, and ITB-2 are used to calculate peak discharge and flood hydrograph shape in this Kadumalik Dam study. The maximum daily rainfall data analysis used the Thiessen Polygon and Arithmetic Mean methods. Of these two frequency analysis methods, the Thiessen Polygon method was chosen. Rainfall transformation into runoff using the FJ MOCK and NRECA methods has been applied in the Kadumalik Dam analysis. Compared to NRECA, the FJ MOCK method with the Thiessen Polygon method for frequency rainfall analysis provided a better performance rating with calibration values of 0.911 for R2, 0.627 for NSE, 0.606 for RSR, 18.141 for RMSE, and 30.764 for PBIAS. The validation values were 0.911 for R2, 0.661 for NSE, 0.582 for RSR, 16.086 for RMSE, and 34.420 for PBIAS. The Kadumalik Dam uses a side-channel spillway model with an ogee spillway crest type. Technically, it is planned based on the design flood discharge Q100 and controlled by discharging the flood discharge Q1000 and QPMF. The purpose of this study is to determine the hydraulic flow behavior that occurs in the numerical model based on CFD with ANSYS Fluent and CFX, along with Flow 3D in the diversion, regulation, and launching channels, to obtain the optimum design of the structures, where the flow classification is steady and transient. From the numerical analysis results, it was found that the water velocity streamline in the launch channel for Q100 with steady flow is 0.1644 – 0.2643 m.s-1, for Q1000 it is 0.2176 – 0.2869 m.s-1, and for QPMF it is 0.1592 – 0.2262 m.s-1. For transient flow, the water velocity streamline in the launch channel for Q100 is 0.1555 – 0.2250 m.s-1, for Q1000 it is 0.1541 – 0.2232 m.s-1, and for QPMF it is 0.1559 – 0.2255 m.s-1. Wet, normal, and dry hydraulic conditions are used in the analysis of the Kadumalik Dam operation pattern. The wet hydraulic condition before the reservoir had an average discharge of 25.51 m3/s, and after the reservoir, the average discharge was 26.89 m3/s, an increase of 5.125%. The normal hydraulic condition before the reservoir had an average discharge of 15.54 m3/s, and after the reservoir, the average discharge was 18.75 m3/s, an increase of 17.105%. The dry hydraulic condition before the reservoir had an average discharge of 1.74 m3/s, and after the reservoir, the average discharge was 7.97 m3/s, an increase of 78.157%.